The Concept Design for Adaptation of Climate Change Through Integrated and Sustainable Flood Infrastructure in the Coastal Area of Pekalongan, Indonesia - Habibi, Suyudi Akbari; Pribadi, Arif Darmawan; Sitorus, Jessica Elisabeth (Geographica Pannonica, 2021)
the sedimentation of river mouths and floods from the watershed to the coastal area of ​​Pekalongan. This study aims to assess the impact of climate change on flood frequency patterns and the contribution of each sub-watershed to the total discharge that occurs, as well as to analyze the effect of increasing sea level that occurs in the coastal area of ​​Pekalongan. The method used in this research hydro-meteorological, hydraulic, and hydrodynamics two-dimensional analysis. The results showed that the climate change that occurred in the coastal area of ​​Pekalongan was indicated by an increase in the average temperature of about 1o Celsius and the trend towards maximum yearly precipitationthat occurred during a period of twenty years had increased (2000-2019 period). An Increasing temperature that occurs has a significant risk to sea-level rise and increasing uncertainty hydrometeorological hazard (tidal flooding). Recommendations from this study arestructuring the drainage system based on an integrated landscape arrangement concept to improve the economy, tourism, social, and environment to achieve sustainable coastal infrastructure.
Keywords: Tidal Floods; Sea Water Rise; Pekalongan